Highly efficient CRISPR/HDR-mediated knock-in for mouse embryonic stem cells and zygotes. (October 2015) - Wang, Bangmei; Li, Kunyu; Wang, Amy; Reiser, Michelle; Saunders, Thom; Lockey, Richard F; Wang, Jia-Wang
The clustered regularly interspaced short palindromic repeat (CRISPR) gene editing technique, based on the non-homologous end-joining (NHEJ) repair pathway, has been used to generate gene knock-outs with variable sizes of small insertion/deletions with high efficiency. More precise genome editing, either the insertion or deletion of a desired fragment, can be done by combining the homology-directed-repair (HDR) pathway with CRISPR cleavage. However, HDR-mediated gene knock-in experiments are typically inefficient, and there have been no reports of successful gene knock-in with DNA fragments larger than 4 kb. Here, we describe the targeted insertion of large DNA fragments (7.4 and 5.8 kb) into the genomes of mouse embryonic stem (ES) cells and zygotes, respectively, using the CRISPR/HDR technique without NHEJ inhibitors. Our data show that CRISPR/HDR without NHEJ inhibitors can result in highly efficient gene knock-in, equivalent to CRISPR/HDR with NHEJ inhibitors. Although NHEJ is the dominant repair pathway associated with CRISPR-mediated double-strand breaks (DSBs), and biallelic gene knock-ins are common, NHEJ and biallelic gene knock-ins were not detected. Our results demonstrate that efficient targeted insertion of large DNA fragments without NHEJ inhibitors is possible, a result that should stimulate interest in understanding the mechanisms of high efficiency CRISPR targeting in general.